Trying to prosume: toward a theory of consumers as co-creators of value - Xie, Chunyan; Bagozzi, Richard P.; Troye, Sigurd V. (Journal of the Academy of Marketing Science, 2008)
One important aspect in the service-dominant logic in marketing is the role of customers as co-creators of value. This role typically involves producing products for own consumption, i.e. what Toffler referred to as “prosumption.” This study explores the motivational mechanisms underlying people’s prosumption propensity. A theoretical framework that incorporates ideas from value research and attitude theory, specifically the “theory of trying” (Bagozzi and Warshaw in Journal of Consumer Research 17:127–140, 1990), is developed and tested in the empirical context of food prosumption. The results based on a survey of 380 households show that global values influence domain-specific values in food prosumption, and domain-specific values then affect attitudes, self-efficacy, and on-going behavior before ultimately shaping intentions to engage in prosumption in the future.